STRATEGI POLITIK ANDRISMAN DALAM PEMILIHAN KEPALA DESA DI DESA TEBING TINGGI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2019 - Desbanita, Irda; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Headman election is the exercise of people's sovereignty in the village in order to elect a headman who is direct, general, free, confidential, and fair. The headman election in Kuantan Singingi Regency was held on Wednesday, September 11, 2019, which was attended by 94 villages in 15 Districts, in Benai District there were 5 villages that will participate in the headman election, namely Banjar Lopak village, Tebing Tinggi, Banjar Benai, Pulau Ingu and Simandolak village. The number of Permanent Voters List (DPT) in Tebing Tinggi village is 1,212 people, consisting of 578 men and 634 women. Andrisman managed to collect the most votes, namely 412 votes. Andrisman is an entrepreneur who is running for the first time as headman. Andrisman and his success team have a work program and excellent vision and mission that led him to win to become headman. Andrisman has 2 organizational experiences, namely as chairman of the Tebing Tinggi village line in 2013-2018 and youth leader ofÂ Tebing Tinggi village in 2013-2017. With this social capital he is able to be known, mingle, and captivate the hearts of the community.This study seeks to answer the researcher's question, namely how Andrisman's political strategy in the headman election in Tebing Tinggi Village in 2019. This research also aims to describe Andrisman's winning strategy in the village head election in Tebing Tinggi village in 2019. This type of research used by the author in this study is descriptive. Data collection techniques are interviews, literature study and documentation. The data analysis technique in this study was carried out qualitatively.The results of the study explained that Andrisman's political strategy in winning the headman election in Tebing Tinggi village was political marketing consisting of 4P of marketing mix, namely Product, Promotion, Place (placement), Price (cost). Political marketing is carried out by campaigning or socializing Andrisman along with his vision and mission and community work programs by visiting residents' houses, campaigning to mosques or surau, visiting farmer and livestock groups.Â Keywords: Political Strategy, Political Marketing, Political Campaign.